A comparison of the imaging features of early stage primary lung cancer in patients treated with surgery, SABR and microwave ablation - Talwar, A; Jenko, N; Sarim, M; Enescu, M; Whybra, P; Willaime, J; Pickup, L; Hickes, W; Gooding, M; Boukerroui, D; Rahman, N; Kadir, T; et al. (BMJ Publishing Group, 2017)
Stereotactic Ablative Radiotherapy (SABR) and percutaneous microwave ablation (PMWA) are now being performed in patients deemed “medically inoperable” with non-small cell lung cancer (NSCLC). The majority of these patients are treated without ground truth histology, relying on imaging to establish the diagnosis. The purpose of this study was to investigate whether there were differences in the visible imaging features including CT Texture Analysis (CTTA) between patients referred for surgery, SABR and PMWA, which might suggest differences in underlying diagnosis.